Uso de recursos alimentares associados à morfologia e disponibilidade de alimentos na Assembleia de Peixes de um lago de Várzea Amazônico - Cornelio, Gilcilene Santana (Instituto Nacional de Pesquisas da Amazônia - INPA, 2023)
Studies on fish morphology and functional ecology are based on the ecomorphological paradigm and may reveal patterns of association between body shape and use of food resources. At the same time, trophic relationships in neotropical fish are strongly influenced by the environment. The aquatic environments of flood plains such as the Amazon basin are subject to a seasonal water regime that promotes strong physicochemical variations and generates changes in the availability of food and shelter against predators. In this way, we sought to verify whether there is an association between morphology and diet that determines an ecomorphological structure in the fish assemblage, as well as to understand the effect of seasonality on this relationship, since it is a determinant of food availability. For this, ecomorphological and dietary information was obtained for the fish fauna of a floodplain lake, the seasonal variation in food availability was estimated from the diet data of all fish captured monthly with stomach contents for two consecutive years. Ecomorphological and dietary similarity was evaluated for 50 species and indicated a positive correspondence between form and use of the food resource. The effect of seasonality on this relationship was evaluated for 11 species that occurred in the low-water and high-water seasons and indicated a null relationship between form and consumed food. However, for low-water, one of the analyzes indicated a weak positive relationship. The effects of seasonal variation on the availability of key items were discussed, as well as the details involved in understanding the ecomorphological relationship and use of the food resource.
Keywords: Alimentação; Ecomorfologia